Working With Refugees' Health During COVID-19-The Experience of Health- and Social Care Workers in Sweden - Elisabeth Mangrio; Elisabeth Mangrio; Slobodan Zdravkovic; Slobodan Zdravkovic; Michael Strange; Michael Strange (Frontiers Media S.A., 2022)
IntroductionIn Sweden, often seen as one of the most egalitarian countries, the COVID-19 pandemic exposed high levels of health inequality, especially harming people with a refugee background. This is also despite Sweden's image as a refugee-friendly country. In this context, the aim of this paper is to better understand how Swedish health- and social workers have reacted to the health- and social needs of refugees during the pandemic. The Swedish case is particularly interesting because, as seen in the paper, health- and social workers had the task of communicating health guidance to refugees who were sometimes more reliant on information from abroad where the consensus on COVID-19 restrictions ran contrary to the approach recommended by the Swedish public health authority.MethodThe study utilizes a qualitative content analysis of 13 in-depth interviews with health- and social workers in Sweden, active in the care of refugees within different kinds of health- and social care settings.ResultsThe analysis showed that healthcare services have remained open during the pandemic but with new precautions at reception areas impacting how refugees access healthcare. As discussed in the article, the shift to digital tools has particularly impacted refugees, worsening already existing barriers to healthcare services faced by those with refugee status. Public health recommendations were poorly designed to the needs of refugees whose living conditions often prevented them from self-isolation and social distancing. Furthermore, Sweden's initially non-restrictive approach to the pandemic instructed health- and social-workers to encourage refugees to take far fewer precautions (e.g., self-isolation, home-schooling, pregnant women to avoid virus hotspots) compared both with European neighbors and the international media typically used by refugees. When Sweden shifted toward a more restrictive approach, health- and social-workers had to revise their guidance in relation to the new recommendations around precautions.ConclusionRefugees have faced increased barriers to maintaining their health and wellbeing during the pandemic that exceed those experienced by the rest of the Swedish population. Refugees have, in general, taken precautions in regard to social distancing and followed recommendations but faced challenges with social distancing due to isolation and crowded living. Public health authorities have often failed to acknowledge that individuals use increasingly diverse sources of knowledge when trying to protect their health, and that not everyone has access to the knowledge needed to access healthcare and social systems. At the same time, there is a need to acknowledge that refugees are sometimes a source of expertise that was ignored by the Swedish health and social system during the pandemic. There is a need for urgent efforts to halt the worsening health conditions for this specific group, but also to counter knock-on societal effects and rising health inequity.